Dall’oggetto all’oggetto. Le radici profonde dell’estetica - Maurizio Vitta (Aisthesis, 2014)
At what stage of development the object becomes a "design object"? The proliferation of everyday objects brought to light the problem of design, but through design we have been aware of the dense and inextricable presence of objects in our everyday experience. These objects, however, to be thought, must first be received, handled, exhausted, covered, used, consumed, handled in their technician structure, questioned, listened, sometimes rejected and sometimes invoked. The life path of the object (need> desire> project> product> commodity> consumption> use> enjoyment> good) is not reduced to a simple linear sequence, the result of a mechanistic view of cultural processes, but it provides a multi-directional map, full of intersections and exchanges, very close to the image of the hypertext.